Comparação dos resultados da contaminação por mesófilos e enterobactérias e dos aspectos operacionais entre os métodos de refile e lavagem de carcaças em abatedouros de frangos do Rio Grande do Sul - Depner, Ronise Faria Rohde (2015)
Resolution n.4 authorizes the use of carcasses washing systems in poultry slaughtering processes to remove contamination from visible gastrointestinal content present in the internal and external surfaces of the carcasses, as an alternative to trimming. The publication of this resolution led to uncertainty as to possible damage to the safety of the product. Thus, the objective of this study was to evaluate the initial results of implementing carcass washing in poultry slaughterhouses of Rio Grande do Sul state and to compare these data with those obtained in the same companies before the change in system, determining if the new system is or not equivalent to the traditional method. Additionally, we sought to evaluate the influence of pressure and water flow from the hoses used in the decontamination of carcasses. The percentages of total and partial condemnation by SIFs, technical data from washers (pressure at the outlet of the water jet spray nozzles and volume water per carcass) and the results from microbiological tests carried out at five slaughterhouses in Rio Grande do Sul state which have already implemented the system were collected. Total and partial condemnation, as well as mesophilic and enterobacteria counts were compared within each slaughterhouse before and after the washing system had been implemented using the chi-square test. The response variables were correlated to each other and to the washing system by means of Spearman correlation analysis, at 5% probability. Also correlation tests were conducted to verify that the different pressures and water flows from washers exerted influence in the decontamination of carcasses. Total condemnation differed between treatments at the slaughterhouse 3 and partial condemnations in Slaughterhouses 2, 3, and 4. The water pressure at the outlet of the sprinkler varied from 3.1 kgf / cm² to 16.3 kgf / cm² and water flow from 0.4 to 1.5 liters per carcass. Visible carcass contamination levels were not different between removal systems, except for Enterobacteriaceae counts at Slaughterhouse 3, which were reduced. There was a positive correlation between the pressure and water flow and the percentage of reduction of mesophilic and enterobacteria. Based on the results obtained in this study, it is clear that both systems were equivalent in the microbiological standpoint, however, if all evaluated washing equipment would use the most efficient parameters, the results of washing system would probably be better than the trimming; the washing system is superior to the trimming from an operational point of view; the pressure has a greater influence on the decontamination of carcasses than the water flow; Additional studies are needed to establish minimum acceptable standards of volume and water pressure for internal and external washing of carcasses in order to improve the method; the feasibility of replacing the carcasses trimming system with the washing system should also be studied in the Department of Final Inspection.